Fundraising Strategies to Optimize Zakat Potential in Indonesia: An Exploratory Qualitative Study - Rahmatina Awaliyah Kasri; Niken Iwani S Putri (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2018)
This paper aims to identify and evaluate differences in the fundraising strategies implemented by different types of zakah institutions in Indonesia, to optimize the country's potential for zakah collection. This study using a qualitative approach, which using semi-structured interviews conducted with zakah organizations in Indonesia. The main finding suggests that differences in fundraising strategies indeed exist. Corporate and government zakah agencies tend to use traditional fundraising strategies, with a partnership approach for collecting zakah and a community-oriented approach for communicating zakah. In contrast, private zakah agencies tend to use market-oriented fundraising strategies allied with retail collection approach and an individual communication approach. It also suggested that the market-oriented fundraising strategy has resulted in higher and more sustainable revenues, indicating consistency with the resource dependence theory of fundraising.DOI: 10.15408/aiq.v10i1.6191